Socioeconomic health inequalities among a nationally representative sample of Danish adolescents: the role of different types of social relations. Issue 9 (21st August 2003) - Due, P; Lynch, J; Holstein, B; Modvig, J
Abstract : Study objective: To investigate the role of different types of social relations in adolescent health inequalities. Design: Cross sectional study. Measures included family social class, indices of social relations to parents, friends, teachers, and school. Setting: Random sample of 55 schools in Denmark. Participants: Nationally representative sample of 5205 students from grades 5, 7, and 9. Main outcome measures: Self reported physical and psychological symptoms. Results: Adolescents from families of lower socioeconomic position reported more physical and psychological symptoms. This ranged from 40% increased odds for multiple physical symptoms among less advantaged girls, to 90% increased odds of multiple psychological symptoms for less advantaged boys. Relationships with friends or teachers showed small social class differences, while strong and consistent social class differences were found in the ways adolescents reported their own and their parents relations to school. For example, girls from families of lower socioeconomic position were more than four times as likely to report their parents unwilling to attend school meetings (odds ratio=4.54, 95% confidence intervals: 2.68 to 7.69). Poorer relations with parents, peers, teachers, and school were all associated with worse health. Patterns of parent-child relations with the school were the greatest contributors to socioeconomic differences in physical and psychological symptoms. Conclusions: The school is one of the first important social institutions directly experienced by children and socioeconomic differences in how adolescents and their parents relate to the school may be part of the cascade of early life influences that can lead to later social and health disadvantage.